hCLOCK Causes Rho-Kinase-Mediated Endothelial Dysfunction and NF-κB-Mediated Inflammatory Responses - Tang, Xiao (Oxid Med Cell Longev, 2015)
Background. The human Circadian Locomotor Output Cycle protein Kaput (CLOCK) gene was originally discovered as a regulator of essential human daily rhythms. This seemingly innocuous gene was then found to be associated with a multitude of human malignancies, via several biochemical pathways. We aimed to further investigate the role of hCLOCK in the hypoxia-oxidative stress response system at the biochemical level. Methods. Expression levels of Rho GTPases were measured in normoxic and hypoxic states. The effect of hCLOCK on the hypoxic response was evaluated with the use of a retroviral shRNA vector system, a Rho inhibitor, and a ROS scavenger by analyzing expression levels of hCLOCK, Rho GTPases, and NF-κB pathway effectors. Finally, in vitro ROS production and tube formation in HUVECs were assessed. Results. Hypoxia induces ROS production via hCLOCK. hCLOCK activates the RhoA and NF-κB signaling pathways. Conversely, inhibition of hCLOCK deactivates these pathways. Furthermore, inhibition of RhoA or decreased levels of ROS attenuate these pathways, but inhibition of RhoA does not lead to decreased levels of ROS. Overall findings show that hypoxia increases the expression of hCLOCK, which leads to ROS production, which then activates the RhoA and NF-κB pathways. Conclusion. Our findings suggest that hypoxic states induce vascular oxidative damage and inflammation via hCLOCK-mediated production of ROS, with subsequent activation of the RhoA and NF-κB pathways.